Location of Industry and Regional Patterns of Business-Cycle Behavior - Vining, Rutledge (Econometrica, 1946)
In a recent paper' we presented the first stage of a statistical inquiry into the nature of the abstraction involved in the use of national series for the description and analysis of business cycles. The results were given of an analysis of one aspect of the cyclical behavior of national income-its percentage rate of change. This rate of change of the national total was interpreted as a parameter of the frequency distribution of the respective rates of change of the component parts of the larger area, and statistics describing a certain pattern of behavior of these distributions were shown. The distributions appear to have a characteristic shape approximating logarithmic normality, and there is a suggestion of a systematic development as the different phases of the business cycle unfold. The skews of the distributions appear to be positive during the period of the expansion when the rate of growth is increasing. When the rate of growth begins to decline, it was tentatively suggested that the skew shifts to a negative and remains a negative through the absolute turning point of national income and during the period when the rate of contraction is increasing. When this rate of contraction begins to decline, the skew of the distribution again shifts to the positive. An attempt was made to rationalize this cyclical evolution of shape of these distributions. It was further noted that the extreme movements from year to year are found generally among the same set of states, there being a tendency evident for the more sparsely settled states that are highly specialized in raw-material production to cluster in the ends of the distribution and, in years of marked change, in the same end of the distribution. It is proposed in the present paper to discuss in more detail the geographical make-up of these annual frequency distributions of regional rates of business change. We think that certain generalizations may be made regarding a regional pattern of short-run business change, and we should like to analyze possible factors that might account for the observable similarities and differences. Our previous discussion of the factors determining the cyclical responsiveness of a given region laid emphasis upon industrial location or specialization and the institutional and physical factors influencing the region's commercial ties. The question we raise now has to do with certain attributes of industrial location that we regard as particularly relevant for regional businesscycle analysis.